Vestiges of lapetan Rifting in the Craton West of the Northern Appalachians - Kumarapeli, P. (Geoscience Canada, 1985)
Summary Plate tectonic models for the evolution of the Appalachians involve a Wilson Cycle of a late Precambrian-early Paleozoic ocean basin - the lapetus. On one side of the lapetus lay the continent of Laurentia, which included the ancient North American landmass. Continental rifting, which initiated the formation of the lapetus in late Hadrynian/early Cambrian times, left its mark on the continental margin of Laurentia in the form of structural damage and rift-related magmatic/volcanic products, and some of these are recognizable from the south-eastern parts of Canadian Shield and the adjacent platform. These include two well-defined aulacogens, zones of step faults parallel to the ancient continental margin and possible fracture zones transverse to the ancient margin. Carbonatite complexes yielding K-Ar ages of approximately 565 Maoccur in both aulacogens. Closely associated with one of them is a prominent dike swarm of probable Hadrynian age.